'PROCLAIMING IT TO GREEKS AND NATIVES, ALONG THE ROWS OF THE CHEQUER-BOARD': READERS AND VIEWERS OF ACROSTICH INSCRIPTIONS IN GREEK, DEMOTIC AND LATIN. (15th March 2017) - Mairs, Rachel
Abstract : Hellenistic and Roman acrostich inscriptions are usually full of verbal and visual clues, which point the reader in the direction of the 'hidden message' contained in the vertical lines of the text. The authors of such inscriptions want their audiences to appreciate the skill that has gone into their composition. There are several complementary ways in which the presence of an acrostich might be signalled to the reader or viewer and their attention directed towards it. These include direct verbal statements, or more subtle allusions, within the text of the inscription. But, even without having read its text, the viewer of an inscription containing a 'hidden message' is often immediately aware that some kind of wordplay is at work. Acrostichs, palindromes and various kinds of word square are all graphically striking, or their appearance may be enhanced to make them more so. Regular spacing, the repetition of the acrostich in a separate column and the use of painted or incised grids are all ways in which the layout of the text on the stone can invite the viewer to play a word game. In some cases, as I will argue in this paper, acrostich makers envisaged—even intended—the participants in this game to include the illiterate as well as the literate.